Towns in the regional policy of activation of peripheral areas - choosing problems - the case of northern Poland - Jacek Sołtys (European Regional Science Association (ERSA), 2011)
In Polish regions there are big differences of the level of development between metropolitan areas (and others surroundings of big cities) and peripheral ones. These differences refere also to the factors and chances of development - in the peripheral areas there are little of them. What could help the activation of those areas is the development of some of the cities, including the localization of the investments. But the development usually requires the support of regional politics resources. In the area of the authors' interests there are problems of regional politics, 1) Which cities should be supported to activate the best peripheral areas of the regions? 2) What kind of transformations of the city space should be supported as part of that politics? Author analyses the problems and relations presented above and designs scenarios of activation of the chosen peripheral areas of provinces in northern Poland.
Keywords: 330